Involving of family members within the program of psychosocial support of women underwent primary psychotic episode - V. Baskina (Kazimierz Wielki University, 2016)
Baskina V. Залучення членів родини в межах програми психосоціального супроводу жінок, які перенесли первинний психотичний епізод = Involving of family members within the program of psychosocial support of women underwent primary psychotic episode. Journal of Education, Health and Sport. 2016;6(10):668-679. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.221663 http://ojs.ukw.edu.pl/index.php/johs/article/view/4113         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7                                                                                                                                      © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.10.2016.   ЗАЛУЧЕННЯ ЧЛЕНІВ РОДИНИ В МЕЖАХ ПРОГРАМИ ПСИХОСОЦІАЛЬНОГО СУПРОВОДУ ЖІНОК, ЯКІ ПЕРЕНЕСЛИ ПЕРВИННИЙ ПСИХОТИЧНИЙ ЕПІЗОД   В. В. Баскіна   Одеський національний медичний університет, Україна   INVOLVING OF FAMILY MEMBERS WITHIN THE PROGRAM OF PSYCHOSOCIAL SUPPORT OF WOMEN UNDERWENT PRIMARY PSYCHOTIC EPISODE   V. Baskina   Odessa National Medical University e-mail: psyhotyp@gmail.com Summary   The problem of supportive programs to women who have had a primary psychotic episode is of top priority for modern psychiatry. The maladaptive characteristics and violations in patterns of family functioning in women with a primary psychotic episode have been established. The author describes the complex of her own of psychosocial support to this category of women directed to their families and shares the experience of its  implementation. Key words: primary psychotic episode, schizophrenia, maladaptive characteristics, family-centered approach.